A Quasi-Experimental Study: Effectiveness of Yoga and Hypnoprenatal Classes in Pregnant Women at High Risk for Maternal Anxiety - Hasnawatty Surya Porouw; Eka Rati Astuti; Ira Titisari; Rahajeng Siti Nur Rahmawati (Poltekkes Kemenkes Palu, 2025)
Background: Anxiety experienced by pregnant women can cause complications during pregnancy and childbirth that can occur in both the mother and the baby. Finger grip and breath relaxation therapy can lower systolic and diastolic blood pressure. One of the movements in yoga is relaxation by gripping fingers and regulating breathing. This movement relaxes the muscles so that it spreads the stimulus to the hypothalamus. The purpose of this study was to analyze the effect of yoga and hypnoprenatal classes on pregnant women with high risk of anxiety in pregnant women, before and after yoga and hypnoprenatal classes, in the treatment and control groups. Methods: This study used a quasi-experimental design with one group pretest posttest design. The sample in this study were pregnant women who met the inclusion criteria, namely pregnant women with a risk age of <20 and >35 years, parity >2, pregnant in the second and third trimesters at the Health Centers throughout Boalemo Regency. The sampling technique used stratified random. In this study, the sample used the proportion formula from Lameshow. The data collection technique uses the HARS scale instrument to measure the level of anxiety of pregnant women which has been tested for validity and reliability internationally. The test used is t dependent test. Results: Based on the mean value of maternal anxiety before and after giving yoga and hypnoprenatal classes is 0.612 and the standard deviation is 0.571. The results of the statistical test obtained a p-value of 0.000. HO is rejected, there is a difference in anxiety scores before and after yoga and hypnoprenatal classes. Conclusion: The conclusion is that there is an influence of yoga and hypnoprenatal classes on pregnant women with high risk of anxiety in pregnant women. There is a significant difference between anxiety before and after giving yoga and hypnoprenatal classes.